Is PLOS ONE Attracting Highly Cited Papers in the Food Sciences? Comparing Authors' Most Cited Work to Their PLOS ONE Articles Published 2006–2016. Issue 1 (2nd January 2018) - Stankus, Tony
ABSTRACT: Since 2007, the Open Access journal PLOS ONE has published 194, 622 expert-reviewed scientific papers, including 85 related to the human food sciences such as food safety, general food science, and nutrition. Seventy-five of their corresponding authors had previously published. Their most cited articles in other journals were identified and citation counts compared against those earned by their PLOS ONE papers. No PLOS ONE food sciences paper has yet been cited more than an author's best effort in the field in other journals. More than half (38) of the 75 PLOS ONE papers studied remain uncited even by their own authors.